2012
DOI: 10.1103/physrevb.85.180508
|View full text |Cite
|
Sign up to set email alerts
|

Fulde-Ferrell-Larkin-Ovchinnikov state in the dimensional crossover between one- and three-dimensional lattices

Abstract: We present a full phase diagram for the one-dimensional (1D) to three-dimensional (3D) crossover of the Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) state in an attractive Hubbard model of 3D-coupled chains in a harmonic trap. We employ real-space dynamical mean-field theory which describes full local quantum fluctuations beyond the usual mean-field and local density approximation. We find strong dimensionality effects on the shell structure undergoing a crossover between distinctive quasi-1D and quasi-3D regimes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Furthermore, the magnitude of the order parameter decreases while the wavelength of the FFLO oscillation grows; this observation holds at all dimensionalities. At the low temperature limit of the phase diagrams, we find good agreement with the zero temperature results of 27 . Throughout the crossover, the lower boundary of the FFLO region in the phase diagram with respect to polarization increases with temperature.…”
supporting
confidence: 83%
“…Furthermore, the magnitude of the order parameter decreases while the wavelength of the FFLO oscillation grows; this observation holds at all dimensionalities. At the low temperature limit of the phase diagrams, we find good agreement with the zero temperature results of 27 . Throughout the crossover, the lower boundary of the FFLO region in the phase diagram with respect to polarization increases with temperature.…”
supporting
confidence: 83%
“…The same qualitative conclusion was reached in [9] using effective field theory and treating the intertube coupling as a perturbation. On the other hand, real-space DMFT studies of coupled chains [10,11] suggested rather that the FFLO state is important in the entire dimensional crossover from quasi-1D to 3D lattices. One reason for differing predictions can be that the stabilization of FFLO in lattices due to nesting [12] is stronger for coupled chains than coupled tubes.…”
Section: Fig 2 (Color Online)mentioning
confidence: 99%
“…Moreover, there is a wide consensus that this system might demonstrate exotic forms of superfluid pairing when subjected to, e.g., a spin population imbalance. The prospects of realizing such forms of conventional and exotic superfluidity in systems of intermediate dimensionality have been discussed broadly in the literature [6][7][8][9][10][11]. However, the role of nonlocal quantum fluctuations remains to a large degree an open question in these systems even in the case of the conventional BCS pairing.…”
mentioning
confidence: 99%
“…Correspondingly, mean-field calculations [30,31] and realspace dynamical mean-field theory (DMFT) for fermions in anisotropic optical lattices find a stable and extended spatially modulated superfluid [32][33][34]. However, such approximations are particularly questionable in 2D.…”
mentioning
confidence: 99%